Small signal impedance analysis of high efficient power devices - Tulbure, Adrian; Hutanu, Constantin; Brezeanu, Gheorghe (2015 International Semiconductor Conference (CAS), 2015)
The semiconductors impedance is a primary electrical parameter that determines the performance of electronic devices and circuits. For this reason many papers [1,] [2], [3] discus the frequency-dependent impedance of semiconductor junctions. Subject of this contribution is the investigation of physical model of the diode and bipolar power semiconductor devices (silicon) in the low frequency range between 0-100kHz. The goal of this contribution is to demonstrate through experimental measurements that the impedance of the power semiconductors depends on the signal frequency, junction's geometry and properties of the electronic structure. In the paper a procedure for computing the equivalent semiconductor impedance has been described and by experiments validated.